1988
DOI: 10.1002/j.2330-8516.1988.tb00277.x
|View full text |Cite
|
Sign up to set email alerts
|

The Equivalence of Scores From Automated and Conventional Educational and Psychological Tests

Abstract: A literature review was conducted to determine the current state of knowledge concerning the effects of the computer administration of standardized educational and psychological tests on the psychometric properties of these instruments. Studies were grouped according to a number of factors relevant to the administration of tests by computer. Based on the studies reviewed, we arrived at the following conclusions: The rate at which test‐takers omit items in an automated test may differ from the rate at which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 28 publications
7
87
0
1
Order By: Relevance
“…First, computer-anxious clients who complete psychological tests administered by computer may produce test scores different from those produced by paper-and-pencil administration (see Hofer & Green, 1985;Honaker, 1987). There is evidence that persons who take tests by computer may alter their rate of omitting items (Mazzeo & Harvey, 1988), increase their "faking good" responses (Davis & Cowles, 1989), and elevate scores on negative affect scales such as those that assess depression and anxiety (George, Lankford, & Wilson, 1990). Second, acceptance of computer-based procedures-from expert systems to CAl and training applications-may also partially depend on mental health professionals' comfort with computer use (Meier, 1985).…”
mentioning
confidence: 99%
“…First, computer-anxious clients who complete psychological tests administered by computer may produce test scores different from those produced by paper-and-pencil administration (see Hofer & Green, 1985;Honaker, 1987). There is evidence that persons who take tests by computer may alter their rate of omitting items (Mazzeo & Harvey, 1988), increase their "faking good" responses (Davis & Cowles, 1989), and elevate scores on negative affect scales such as those that assess depression and anxiety (George, Lankford, & Wilson, 1990). Second, acceptance of computer-based procedures-from expert systems to CAl and training applications-may also partially depend on mental health professionals' comfort with computer use (Meier, 1985).…”
mentioning
confidence: 99%
“…These differences could introduce construct-irrelevant variance due to the testing medium. The investigation of that question has received significant attention (Gallagher et al 2002;Horkay et al 2006;Mazzeo and Harvey 1988;Powers et al 1994;Puhan et al 2007;Wolfe et al 1993). …”
Section: Medium Effectsmentioning
confidence: 99%
“…Since computer is the medium of CBLT which can be presented interactively through many channels, the interaction and multimedia effects may also affect test performance and can be regarded as a potential element of CBLT validity. The study conducted by Mazzeo and Harvey (1988) found out that the number of screens, screen size, font and letter size, image resolution, and other complex ways of presentation could have significant impact on CBLT performance. McKee and Levinson (1990) pointed out that those computer-related modes of item presentation probably had greatly changed the nature of items and that a PBLT and the relevant CBLT probably were not testing the same thing.…”
Section: Impact Of Audio-visual Cognitive Competencementioning
confidence: 99%